2021
DOI: 10.1159/000514331
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise as a Resilience Factor to Mitigate COVID-Related Allostatic Overload

Abstract: Introduction: The long-lasting threat of COVID-19 makes it necessary to explore strategies to improve coping skills which enable us to master a balanced life in the face of adversity. Objective: To unravel the most challenging aspects of COVID-19 in a nonclinical adult population and identify predictors of lost balance and consequent allostatic overload (AO). We examined the role of regular, moderate-intensity formula aerobic exercise (312 meridian exercise) in preventing allostatic overload through increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…However, the well-being of British general practitioners was comparable to the local population, and GPs above 55 years showed higher hope and optimism than their younger counterparts [ 31 ]. Our sample showed comparable levels of mental and social well-being during the COVID-19 pandemic to a community sample [ 21 ]; however, anxiety and hostility scored higher, probably referring to the high level of additional professional stress load. Most of the GPs ensured time regularly for recreation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, the well-being of British general practitioners was comparable to the local population, and GPs above 55 years showed higher hope and optimism than their younger counterparts [ 31 ]. Our sample showed comparable levels of mental and social well-being during the COVID-19 pandemic to a community sample [ 21 ]; however, anxiety and hostility scored higher, probably referring to the high level of additional professional stress load. Most of the GPs ensured time regularly for recreation.…”
Section: Discussionmentioning
confidence: 56%
“…We applied these tools – in accordance with previous research [ 20 , 21 ] – to measure COVID-related allostatic overload ( Table 1 ). Besides measuring individual stressors, our primary focus was on COVID-related allostatic overload.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, exercise has proven its effectiveness in dysautonomia and POTS, quite frequent among people with post-COVID-19 syndrome, by restoring upright hemodynamics, normalizing renal-adrenal responsiveness, and improving quality of life [ 122 , 123 ]. In addition, recent cross-section studies support the need of regular moderate exercise as a resilience factor to reduce COVID-related allostatic overload by improving mental and physical well-being [ 124 ].…”
Section: The Potential Role Of Exercise In Post-covid-19 Syndromementioning
confidence: 99%
“…Therefore, it is necessary to take measures to counteract the effects of sleep deprivation and to improve cognitive performance during sleep deprivation. Physical exercise involves the stretching of bones by muscles and the consumption of energy, and is a planned and repetitive physical activity designed to promote health, and improve motor skills (Eöry et al, 2021 ). Studies have shown that physical exercise is an important means to ensure physical and mental health, which can reduce the incidence of physical diseases (such as cardiovascular disease and obesity, etc.)…”
Section: Introductionmentioning
confidence: 99%